New chalcone compound as a promising antileishmanial drug for an old neglected disease: Biological evaluation using radiolabelled biodistribution. (June 2018) - Sousa-Batista, Ariane de J.; Philipon, Cíntia I.M. Silva; de Souza Albernaz, Marta; Pinto, Suyene Rocha; Rossi-Bergmann, Bartira; Santos-Oliveira, Ralph
Highlights: Development of labelling process for chalcones using 99m Tc. Biological evaluation of a new chalcone. Abstract: Objectives: Treatment of leishmaniasis remains a challenge, especially due to the need for multiple painful injections, the toxicity of current drugs against the disease, their lack of efficacy and, lately, drug resistance. The aim of this study was to demonstrate the biological behaviour of 3-nitro-2ʹ-hydroxy-4ʹ, 6ʹ-dimethoxychalcone (CH8) in a murine model of cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL). Methods: To evaluate its biological behaviour, compound CH8 was radiolabelled with technetium-99m ( 99m Tc) using the direct reaction. Groups of animals infected with ether Leishmania infantum (as a model for VL) or Leishmania amazonensis (as a model for CL) were administered CH8- 99m Tc orally or subcutaneously, respectively, and its biodistribution was evaluated. Results: Oral administration of CH8- 99m Tc resulted in poor absorption. However, the absorbed drug was expressively taken up in the blood and liver, the main organ infected in VL. CH8- 99m Tc administered by the subcutaneous route showed a poor distribution and significant uptake in the left ear, suggesting a local effect in the skin. In addition, the VL and CL infection models did not considerably alter the biodistribution profile by the oral and subcutaneous routes, respectively. Conclusion: These results suggest that CH8 is a promising candidate for oral treatment of VL and for intralesional treatment of CL, showing a prominent local effect.